Effect of the concentration and size of suspended particulate matter on oil-particle aggregation. (April 2020) - Qi, Zhixin; Yu, Yue; Yu, Xinping; Li, Wenxin; Fu, Sinan; Xiong, Deqi
Abstract: After spill, the dispersed oil droplets may collide with suspended particulate matter in the water column to form oil-particle aggregates (OPAs) in turbulent environments. It may be an effective pathway to stabilize the oil by taking advantage of the particulate matter to clean up the contaminated waters. A theoretical model in Payne et al. (2003) is adopted to describe the oil-particle aggregation, and a solution method is proposed and validated against a group of experiments. The effect of the particle size and mass concentration on the aggregation has been examined quantitatively in detail. The particles and the oil droplets are consumed at a fixed ratio. Under the same mass concentration, smaller particles can trap more oil droplets, while larger particles tend to interact more quickly with the oil. The oil-particle aggregation rate and the oil trapping efficiency mainly depend on the particle concentration. The theoretical model is applied to predict the decrease of the dispersed oil in nearshore environments, based on the parameters obtained from the experiments. It is efficient to promote the oil-particle aggregation by increasing the particle concentration in the closed bay. In the open sea, the decrease of the dispersed oil can be effectively enhanced by increasing the particle concentration when it is below 0.50 kg/m 3 . The information presented in this paper can serve to predict the fate of the dispersed oil in coastal waters and provide technical support for oil spill management strategies. Highlights: Suspended particles and oil droplets are consumed at a fixed ratio to form OPAs. Particle concentration significantly affects the oil-particle aggregation rate and oil trapping efficiency. Smaller particles trap more oil droplets, while larger ones aggregate more quickly. Increase of particle concentration promotes the oil-particle aggregation in the bay. Increase of particle load from below 0.50 kg/m 3 expedites the oil decay in the open sea.